Prevalence of Female Sexual Dysfunction in Iran: A Meta-Analysis Study - Hosseini Tabaghdehi 1, Monirolsadate; Keramat 1*, Afsaneh; Khosravi 2, Ahmad (Shahroud Journal of Medical Sciences, 2017)
Background: Sexual dysfunction in women is very common and it affects physical and mental health. Several studies have been conducted in Iran in order to investigate the prevalence of female sexual dysfunction. However, there is a remarkable diversity among the results. This meta-analysis was conducted to estimate the overall prevalence of female sexual dysfunction in Iran.Methods: International and national electronic databases were searched up to June 2016, which included MEDLINE, Science Citation Index Expanded, Scopus, ISI, Google Scholar, IranDoc, SID, MagIran, and IranMedex, as well as conference databases. Furthermore, reference lists of articles were screened and the studies’ authors were contacted for additional references. Cross-sectional studies addressing the prevalence of female sexual dysfunction were included in this meta- analysis.Results: We assessed eight separate studies involving 5,778 participants overall, of which 2,335 had sexual dysfunction. Overall prevalence rate of female sexual dysfunction was 0.48 (0.38, 0.59).Conclusions: Various prevalences of sexual dysfunction have been reported in different studies. Furthermore, despite many studies conducted addressing the prevalence of female sexual dysfunction, there is however a remarkable diversity between the results. Thus one can hardly give a precise estimation of the prevalence rate of female sexual dysfunction in Iran at the moment.